TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN SIKAP PENGGUNAAAN MEDIA SOSIAL (STUDI PADA MAHASISWA JURUSAN ADMINISTRASI NIAGA POLINEMA) - Erlangga Andi Sukma (Adbis: Jurnal Administrasi dan Bisnis, 2018)
This study examines individual adoption behavior of the most popular social networking site Instagram. The influences on the attitude toward using social networking based on individual’s perceived ease of use (PEU), perceived usefulness (PU) and trust is empirically examined with a primary data set of 95 students of Business Administration at State Polytechnic of Malang, users of Instagram gathered from a questionnaire survey. The results demonstrate that the revised social media TAM model proposed in this study supports all the hypotheses of attitude toward using social media. The results of this study provide evidence for the importance of additional key variables to TAM in considering user engagement on social media sites and other social-media-related business strategies.